Going from a private to public company and the impact on revenue recognition - Jecrois Madrid, Alexandra (Kansas State University, 2014)
PS International (PSI) is an international trading company that specializes in the trading of bulk agricultural commodities. It has global strength to both export and import a variety of agricultural products using affiliated offices positioned throughout the world. To adapt to competitive pressures, advancements in technology, and economic conditions, privately-held companies are re-structuring their business by acquiring or partnering/merging with other companies. This results in a redefinition of the assets, operations, and relationships with the stockholders. The acquisition of a private company by a publicly held company creates unique issues because the newly acquired private company must meet SEC accounting standards. One example of this is the acquisition of PSI by Seaboard Corporation, a publicly traded company. In 2010, the owners of PSI sold fifty percent share of the company to Seaboard Corporation. Today Seaboard Corporation owns 80% of PSI. This research problem is based on the challenges that the acquisition of a private company by a public company faces. The focus of the analysis was on the accounting changes in the area of accounts receivable, in particular when revenue is recognized. PSI used cash basis accounting and Seaboard is required to use an accrual method that required a modification in PSI’s accounting system. This research investigates the impact of those changes on PSI’s accounts. The main factors used for comparison of revenue recognition under the cash and accrual method were departure date, transit time and payment terms. The comparisons were based on a data from 196 deliveries made in 2012. In the cash method, revenue was recognized for all the transactions during the month of shipment departure. This revenue was included whether or not the transactions were paid in full and whether or not the cargo arrived at its destination in the same month. In the accrual method, only 20.92% of the transactions were recognized in the current month of shipment, because revenue must be earned and realizable to be consistent with the SEC criteria, otherwise revenue must be deferred until the payment is collected. Therefore, as the result of applying either the cash or accrual method in the income statement, transaction will be recorded as accounts receivables and/or deferred transactions. With the application of the accrual method, the working capital calculation and the annualized margin must take more into consideration by managers, the trading staff and logistic staff.
Keywords: Revenue recognition; Sarbanes-oxley; GAAP; Accrual accounting; Agribusiness